p16(INK4A) as a marker for cervical dyskaryosis: CIN and cGIN in cervical biopsies and ThinPrep™ smears - Murphy, N (Copyright 2003 Journal of Clinical Pathology, 2003)
Aim: To examine the potential of p16(INK4A) as a biomarker for dysplastic squamous and glandular cells of the cervix in tissue sections and ThinPrep™ smears. Methods: Immunocytochemical analysis of p16(INK4A) expression was performed on 22 normal cervical tissue samples, five cervical glandular intraepithelial neoplasia (cGIN), 38 cervical intraepithelial neoplasia 1 (CIN1), 33 CIN2, 46 CIN3, and 10 invasive cancer cases (eight squamous and two adenocarcinomas). All samples were formalin fixed and paraffin wax embedded, and immunohistochemical analysis was carried out using a mouse monoclonal anti-p16(INK4A) antibody after antigen unmasking. The staining intensity was assessed using a 0 to 3 scoring system. In addition, the expression status of p16(INK4A) was examined in 12 normal ThinPrep smears, one smear exhibiting cGIN, and a total of 20 smears exhibiting mild, moderate, and severe dyskaryosis. Human papillomavirus (HPV) detection was carried out using a modified SYBR green assay system. Fluorogenic polymerase chain reaction (PCR) and solution phase PCR were used for specific HPV typing. Results: p16(INK4A) immunoreactivity was absent in all normal cervical tissues examined. Dysplastic squamous and glandular cells were positive for p16(INK4A) expression in all cases included in this study, except for one CIN3 case. p16(INK4A) expression was mainly nuclear in CIN1 cases, and both nuclear and cytoplasmic in CIN2, CIN3, cGIN, and invasive cases. All cases positive for HPV expressed the p16(INK4A) protein, although not all cases found positive for p16(INK4A) were HPV positive. In general, the p16(INK4A) staining intensity was lower in cases negative for HPV or those containing a low risk HPV type. Conclusion: This pattern of overexpression demonstrates the potential use of p16(INK4A) as a diagnostic marker for cervical squamous and also glandular neoplastic lesions. In addition, the technique can be used to identify individual dyskaryotic cells in ThinPrep smears. Thus, p16(INK4A) is a useful marker of cervical dyskaryosis.